Analysis of Traditional Care of Postpartum Mothers - Pibriani Pibriani; Lisa Trina Arlym; Retno Widowati (Indonesian Journal of Global Health Research, 2025)
Traditional postpartum care is still practiced in Cimanggu District. Based on 2024 data, 27 mothers experienced problems during the postpartum period caused by the use of bengkung, consumption of sambel peupeuh, application of campuh, and practicing the traditions of nyanda and sangsurkeun. Several factors influencing the practice of traditional care according to theories and previous studies include knowledge, attitude, culture, family support, and health worker support. Objective to analyze traditional postpartum care in Cimanggu District, Pandeglang Regency, Banten. This research used a mixed-methods approach with a sequential explanatory strategy design. The sample consisted of 88 postpartum mothers selected using purposive sampling. The instruments used were questionnaires and open interviews. Data were analyzed using Chi-Square statistical tests, multiple logistic regression, and qualitative analysis. There was a significant relationship between knowledge, attitude, culture, family support, and health worker support with traditional postpartum care (p-value < 0.05). Qualitative findings showed that the better the mother’s knowledge and attitude, the stronger the cultural influence, and the greater the family and health worker support, the higher the tendency for mothers to practice traditional care in a safe and sustainable way. The most dominant factor in traditional postpartum care was health worker support, with an OR of 24,064.